TRADISI MAKAN BAJAMBA DI MINANGKABAU: STUDI LIVING HADIS - Erlina, Erlina; Nasrulloh, Nasrulloh (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This study aims to analyze the form of living hadith in the tradition of eating bajamba in Minangkabau in order to strengthen its philosophy, namely the custom of basandi shara', shara' basandi kitabullah. This research is a qualitative research of library studies. Collecting the data were through a theoretical study of primary and secondary sources in the form of books, trusted news, and publication journal articles. To analyze the data, researchers perform classification, analysis, comparison and synthesize the data. The results of the study show that: the living hadith in the bajamba tradition is seen in the implementation of the hadith about the recommendation to eat together, starting the meal when permitted by the host, placing food on the floor instead of at the table, eating with the right hand and eating food that is in front of it alone, eating from the side of the plate, not from the middle, not allowing food fillings to drop, and the implementation of the hadith about washing hands to clean up the remnants of food after eating.